Investigating understanding the nature of science - Veena Prachagool; Prasart Nuangchalerm (International Journal of Evaluation and Research in Education (IJERE), 2019)
The survey method was employed for investigating understanding nature of science (NOS) between general science education and science pre-service teachers. Independent t-test and two-way ANOVA were used for testing hypothesis. Results found that both of two programs rated understanding NOS ranges disagree and highly agree levels in different items. The item ‘scientists work in their laboratory, even though social needs are not influence to scientists’, disagree for general science education but agree for science program. The post-hoc test indicated that there were not differences by mean scale of two programs. There was no interaction between group and components of NOS. The post-hoc test also indicated that not found the differences in each component among scientific worldview, scientific inquiry, and scientific enterprises. However, three components of NOS must incorporate to teacher preparation program for making community of science and literate person as well as philosophy of science education.